FOREIGN EXCHANGE INDEX AND MACROECONOMIC: PANDEMIC COVID-19 IN INDONESIA - Hariyani, Diyah Santi; Ratnawati, Tri; Rahmiyati, Nekky (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This research aims to analyse the influence of foreign exchange index and macroeconomic globalization which includes SSEC, S&P BSE Sensex, exchange rate, world gold price, and inflation on the CSPI before and during the government decided to lockdown due to the spread of Covid-19 virus. Sampling-based on time series data with observation periods from 8 January 2019 to 9 June 2020, data analysis techniques used regression SPSS. The results concluded that the Shanghai Stock Exchange Composite has a significant effect on the CSPI, the S&P BSE Sensex significantly influential to the CSPI, the exchange rate has a significant effect on the CSPI, the world gold price significantly negative to the CSPI, inflation has a significant negative effect on the CSPI before and during the Pandemic Covid-19 in Indonesia Keyword: CSPI, Exchange Rate, Inflation, S&P BSE Sensex, World Gold Price